Diagnostic and treatment alternatives for the correction of facial asymmetries: A literature review. - Rojas Reyna, Braulio Rafael (2022)
Facial symmetry refers to a complete coincidence of each facial component on the sagittal plane, while asymmetry refers to the bilateral difference between these components. The presence of perfect bilateral symmetry is almost never present in human, so it is more common for individuals to predominate facial asymmetry. However, ocassionally, significant facial asymmetry results not only in functional but also in aesthetic problems. This research seeks to determine the alternatives, diagnosis and ideal treatment plan for the correction of each type of facial asymmetry through orthognathic surgery. For this purpose, a review of articles published between 2015 to date was carried out. Selecting those that were focused on describing or evaluating facial and dentofacial symmetry and asymmetry, type of diagnosis or treatment plan, including clinical cases. The Google search engine, SciELO and databases of medical interest, such as PubMed, PMC and Medigraphic were used. According to the research and treatments carried out during the last few years in the dental clinic, it has been proven that orthognathic treatment accompanied by previous planning is the best option for the management of skeletal facial asymmetries.